Influence of Additional Feeding of Succous Goats on Indices of Natural Resistance of the Organism of Goats, Milk Productivity and on the Development of Goatlings (Texas Journal of Multidisciplinary Studies, 2023)
The article discusses the regularities of the influence of additional feeding to the pasture ration during the period of pregnancy, the first flow of the Saanen breed on the basis of indicators of natural resistance and biochemical blood tests of the obtained goatlings. It was found that the change in the humoral factors of natural resistance in mothergoats occurs mainly under the influence of factors of feeding, and the cellular factors of natural resistance of the first flow have relatively constant values and are within the physiological norm. The content of total protein and its fractions changes slightly. In accordance with the nutrients consumed by the mothers, the indices of natural resistance in the goatlings are subject to change.